CAPACITY BUILDING ORGANISASI POSKESTREN MAMBA’UL HUDA - Multazam Mansyur Addury; Abdul Halim Rofi’i (Sekolah Tinggi Agama Islam Syubbanul Wathon Magelang, 2021)
In the form of empowerment of facilities and infrastructure in Islamic boarding schools, Mamba'ul Huda Islamic Boarding School, Kaliabu, there are already available facilities for students in the health sector with the existence of Islamic Boarding School Health Posts or often referred to as Poskestren. The service aims to study and analyze the capacity building of the Mamba'ul Huda Kaliabu's poskestren organization. The approach used in this study is ABCD. ABCD is used in this service because it is considered appropriate to solve problems according to the assets owned by certain groups or institutions. The method used in this service is by holding deliberation, mentoring, and training with the management of the Mamba'ul Huda poskestren. The service results can be concluded that the capacity building of the Mamba'ul Huda Kaliabu poskestren organization has developed well in health services. However, organizing and increasing the knowledge of Husada students still requires supervision, training in the fields of organization, leadership, and skills of Husada students. The author hopes that after this service, they can develop the insight of Husada students in managing the Mamba'ul Huda Poskestren.